The impact of Enterprise Risk Management (ERM) on firm performance of small and medium enterprises (SMEs) - Lukyanchuk, Genrikh / GL (2013)
This research paper is focused on the analysis of Enterprise Risk management (ERM) in small and medium enterprises (SMEs). Measures that reflect the possible use of risk management are calculated and the results are based on their impact on performance and volatility of cashflow. Also, a relation between the two latter variables is analyzed and the conclusions on how they relate while implementing proper risk management techniques is drawn. Likewise, useful implementations are given underlining the scientific value of this work.